Effectiveness of Pumpkin Pudding and Pineapple Pudding on Blood Glucose Levels in Diabetic Patients - Yosi Irene Putri; Hildayati Zainia Yuliya; Hasneli Hasneli (Journal of Nutrition Science, 2023)
Hyperglycemia, often known as high blood sugar, is a disease that causes diabetes. Free radicals are produced as a result of hyperglycemia. Due to elevated blood sugar levels, the antioxidant content in pumpkin and pineapple can prevent the formation of free radicals. Reducing blood glucose levels as a result. The purpose of the study is to determine whether giving diabetics pumpkin and pineapple pudding lowers their random blood glucose levels.This type of research is a quasi-experimental design with a pretest and posttest with control group. The sampling technique used was purposive sampling with a sample of 30 diabetic patients, consisting of 2 groups (which were given pumpkin and pineapple pudding): each consisted of 15 patients. Provision for 7 days in a row as much as 250 gr. Random blood glucose levels were measured one day before and after the intervention using the Blood Glucose test. Data analysis using Wilcoxon and Mann Whitney test. The results of this study showed a significant difference in decreasing random blood glucose levels in patients who were given pumpkin pudding (P1) and patients who were given pineapple pudding (P2) between initial and final random blood glucose levels. This research also shows the effectiveness of pumpkin and pineapple pudding in lowering random blood glucose levels.